Study on Ammonia-induced Catalyst Poisoning in the Synthesis of Dimethyl Oxalate - Hua-wei Liu; Sheng-tao Qian; Er-fei Xiao; Ying-jie Liu; Jun Lei; Xian-hou Wang; Yu-hua Kong (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
On an industrial plant, we observed and examined the ammonia-poisoning catalyst for the synthesis of dimethyl oxalate (DMO). We investigated the catalytic activity in response to the amount of ammonia and revealed the mechanism of such poisoning by X-ray photoelectron spectroscopy (XPS) characterization. Our results show that only 0.002% ammonia in the feed gas can significantly deactivate the Pd-based catalyst. Two main reasons were proposed: one is that the competitive adsorption of ammonia on the active component Pd hinders the carbon    monoxide (CO) coupling reaction and the redox cycle between Pd0 and Pd2+; and the other is that the high-boiling nitrogen-containing amine compounds formed by reacting with ammonia have adsorbed on the catalyst, which hinders the progress of the catalytic reaction. The deactivation caused by the latter is irreversible. The catalytic activity can be completely restored by a low-temperature liquid-phase in-situ regeneration treatment. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).